Experimental analysis of short concrete column under hygrothermo-mechanical accelerated aging - Nacera Hassani; Hocine Dehmous (Fracture and Structural Integrity)
Concrete is still considered to be very durable material for a long time. However many constructions have shown degradations during their service life. To ensure safety, stability and serviceability of civil engineering structures, understanding of deterioration processes and their effect on the residual structural load capacity is necessary. This paper is based on the experimental study of short prismatic concrete columns under the hygrothermo-mechanical aging process. To investigate the effects of the exposure conditions on the strength of specimens, combined Ultrasonic Pulse Velocity testing and compression loading testing was used. It can be observed from the results obtained in this work that the ultrasonic pulse velocity measurements agree well with the experimental results obtained from the compression loading testing. Results indicate that in first time, degradation of specimens occurs slightly. After that the degradation becomes notable. It also indicates that the degradation due to the combined effect of the hygrothermo-mechanical aging process is higher than when we consider hygrothermal and mechanical process separately.